The competencies of global managers in multinational corporations (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
Purpose: Multinational corporations have become one of the most important drivers of continuous globalization and constant developments in the global economy. Doing the business globally, across borders in diversified environment they have given rise of and put an emphasis on such concepts as “global managers” and cross-cultural management. The aim of the article is to identify of the key competences of global managers in cross-cultural management of multinational corporations. Design/methodology/approach: The methodology for this study is a review of the relevant literature on global management competencies. The authors looked into the knowledge, competencies and skills of global mangers in multinational environment. Findings: A critical analysis of the literature enabled an identification of the key competencies of successful global managers such as cultural self-awareness, intercultural communication or global mindset. It showed also the role of cross-cultural management in multicultural enterprises. Research limitations/implications: The literature review conducted in this paper reveals the gap in the research on global managers’ competencies and their impact on the performance of multinational corporations. Original value: The competences of global managers of multinational corporations are not studied very often; however they seem to be very important source of success of the MNCs. The literature review gives an insight to the current state of knowledge in this field required for managers working in culturally diverse teams in multinational corporations.